EFEKTIVITAS ORGANISASI DISKOMINFOTIK PEMPROV DKI JAKARTA DALAM MENGGUNAKAN MEDIA SOSIAL INSTAGRAM @DKIJAKARTA UNTUK MEWUJUDKAN KETERBUKAAN INFORMASI BERKUALITAS DI JAKARTA - Dwi Aldi Aurora, Danissa; Nurcahyanto, Herbasuki (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2025)
The digital era brings openness of information as a critical factor in establishing transparent and accountable governance. The Jakarta Provincial Government, through the Office of Communication, Information, and Statistics (Diskominfotik), utilizes the Instagram account @dkijakarta as a public communication platform to achieve high-quality information transparency. However, challenges such as low responsiveness to public feedback and limited use of interactive features hinder the creation of more effective two-way interactions. This study aims to analyze the effectiveness of Diskominfotik DKI Jakarta in managing the Instagram account @dkijakarta using a mixed methods approach with an exploratory sequential design. Data were collected through in-depth interviews and closed surveys to evaluate goal achievement, integration, and adaptation to digital trends. The findings indicate that while Instagram is proven to be an effective platform for disseminating information, the response to public feedback remains suboptimal. Limited utilization of interactive features, such as Q&A sessions and live streaming, presents a major challenge in fostering more participatory information transparency. This study recommends the implementation of comprehensive social media management SOPs, including guidelines for response time, trend-based content governance, and the use of social media analytics for performance evaluation. These measures are expected to enhance transparency and responsiveness in public information dissemination through more innovative and interactive social media strategies.